2010
DOI: 10.1016/j.jphotochem.2010.07.024
|View full text |Cite
|
Sign up to set email alerts
|

What is Degussa (Evonik) P25? Crystalline composition analysis, reconstruction from isolated pure particles and photocatalytic activity test

Abstract: Anatase and rutile crystallites were isolated from Degussa (Evonik) P25 by selective dissolution with a hydrogen peroxide-ammonia mixture and diluted hydrofluoric acid, respectively, and used as standard samples for calibration curves of X-ray diffraction analyses.The results showed that P25 contains more than 70% anatase with a minor amount of rutile and a small amount of amorphous phase. The composition anatase/rutile/amorphous could be determined by analysis of P25 mixed with an internal standard, nickel(II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

42
574
3
15

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 835 publications
(634 citation statements)
references
References 19 publications
42
574
3
15
Order By: Relevance
“…These particles agglomerate forming aggregates with different shapes and morphologies, which influence the surface roughness, haze and transparency of the bulk material [26]. The approximate size of the P25 nanoparticles is between 15 and 30 nm, which is in accordance with values presented in literature [27]. Fig.…”
Section: Photocatalysts Characterizationsupporting
confidence: 88%
“…These particles agglomerate forming aggregates with different shapes and morphologies, which influence the surface roughness, haze and transparency of the bulk material [26]. The approximate size of the P25 nanoparticles is between 15 and 30 nm, which is in accordance with values presented in literature [27]. Fig.…”
Section: Photocatalysts Characterizationsupporting
confidence: 88%
“…The commercial photocatalyst Degussa (Evonik) P25 was used as a reference sample because of its high level of activity in various photocatalytic reactions ensuring clear discussion of the influence of reaction parameters on photocatalytic activity of DAPs [40].…”
Section: Photocatalytic Reactionsmentioning
confidence: 99%
“…In our opinion it is more likely that the observed changes in phase composition at relatively low calcination temperature could correspond to the transformation of an amorphous phase into anatase. Ohtani et al (34) found that P25 photocatalyst contains anatase, rutile and small amount of amorphous phase. The XRD analysis does not directly confirm the presence of an amorphous phase in phase composition.…”
Section: Photocatalytic Activity Measurementsmentioning
confidence: 99%